1973
DOI: 10.1111/j.1432-1033.1973.tb03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Subunit Structure of Aspartokinase III of Escherichia coli K12

Abstract: The lysine-sensitive aspartokinase I11 of Escherichia coli K12 is composed of subunits of 50000 molecular weight. By determination of terminal residues and inspection of tryptic hydrolysis products, the subunits appear identical. The native enzyme is a dimer of 105000 molecular weight in the presence of 0.15 M KC1 in the absence of lysine. Two types of equilibrium can be evidenced : an association at high ionic strength in the presence of lysine leading to a tetrameric form and a dissociation towards monomer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

1975
1975
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…Consistent with reports of lysine-induced AKIII tetramer formation (22,23), association of two dimers is apparent across a crystallographic 2-fold axis of the T-state AKIII (Fig. 1D).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with reports of lysine-induced AKIII tetramer formation (22,23), association of two dimers is apparent across a crystallographic 2-fold axis of the T-state AKIII (Fig. 1D).…”
Section: Resultssupporting
confidence: 89%
“…A change in the oligomeric state of AKIII to a homotetramer on lysine binding has been suggested (18,22,23). Mutational analyses of the C-terminal AKIII region indicate this to be the site for lysine binding (24,25).…”
mentioning
confidence: 99%
“…However, native gel electrophoresis studies suggested that the plant enzyme exists as a functional dimer in solution (Mas-Droux et al, 2006) and earlier analytical ultracentrifugation and gel-filtration studies clearly established the dimer as the catalytically active unit of the monofunctional AK in Escherichia coli (ecAKIII; Richaud et al, 1973. Gel-filtration and dynamic light-scattering studies were conducted on mjAK to address the discrepancy in the quaternary structure of AK between that observed in the crystal and that reported in solution.…”
Section: Gel Filtration and Dynamic Light Scatteringmentioning
confidence: 99%
“…The AKs from Escherichia coli include the bifunctional AK-HDH I which assembles into a 360 kDa tetrameric complex (Veron et al, 1985), while the second bifunctional enzyme (AK-HDH II) is found as a dimer in solution (Dautry-Varsat et al, 1977). The monofunctional AK III from E. coli assembles into a smaller dimer of only 96 kDa (Richaud et al, 1973). Additional complexity is evident in the regulation of the AKs, which are mediated by the end products of the pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The capacities of the different immunoadsorbents for their homologous antigens were determined as previously reported (18) and are expressed in nanomoles of subunits bound per milliliter of packed immunoadsorbent. The respective molecular weights of the subunits of the enzymes which will be shown to be retained are the following: aspartokinase I-homoserine dehydrogenase I = 86,000 (19); aspartokinase I fragment = 48,000 (10); proteolytic homoserine dehydrogenase I fragment = 55,000 (10); aspartokinase II-homoserine dehydrogenase II = 86,000 (unpublished results); aspartokinase III = 52,000 (20); homoserine kinase = 30,000 (Burr, in preparation).…”
mentioning
confidence: 94%